2016
DOI: 10.1080/16506073.2016.1205658
|View full text |Cite
|
Sign up to set email alerts
|

Acculturative stress and experiential avoidance: relations to depression, suicide, and anxiety symptoms among minority college students

Abstract: Although college campuses represent strategic locations to address mental health disparity among minorities in the US, there has been strikingly little empirical work on risk processes for anxiety/depression among this population. The present investigation examined the interactive effects of acculturative stress and experiential avoidance in relation to anxiety and depressive symptoms among minority college students (n = 1,095; 78.1% female; Mage = 21.92, SD = 4.23; 15.1% African-American (non-Hispanic), 45.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…Similarly, the population which has no religious belief (n = 3,242) is also significantly higher than that has a religious belief (n = 379). Many studies support the evidence that minorities in a population are more likely to suffer depression 29,30 . Maybe more efforts need to be done to support the minority students in the universities.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, the population which has no religious belief (n = 3,242) is also significantly higher than that has a religious belief (n = 379). Many studies support the evidence that minorities in a population are more likely to suffer depression 29,30 . Maybe more efforts need to be done to support the minority students in the universities.…”
Section: Discussionmentioning
confidence: 86%
“…While the AAQ-II's psychometric properties have been supported in previous work, the samples have primarily consisted of Non-Hispanic White (NHW) or White European individuals. Assessment of the AAQ-II's psychometric properties among racially/ethnically diverse samples is particularly important given that cultural beliefs and acculturative stress have been shown to impact experiential avoidance (Su, Wei, & Tsai, 2014;Zvolensky, Jardin, Garey, Robles, & Sharp, 2016). Specifically, a recent study found that among Hispanic/Latinx (H/L) individuals that were high on experiential avoidance also experienced significantly more acculturative stress as compared to those who were lower on experiential avoidance.…”
Section: Introductionmentioning
confidence: 99%
“…A study found that acculturative stress was related to greater levels of suicidal symptoms, social anxiety, and anxious arousal among minority college students with higher, but not lower, levels of experiential avoidance (Zvolensky et al 2016).…”
mentioning
confidence: 99%